Design, Modeling, and Simulation of Two-Piece Trapezoidal Piezoelectric Devices for Sensing and Energy Harvesting - Nan Chen; Vishwas Bedekar (Advances in Materials Science and Engineering)
The objective of the research is to design a high power energy harvester device through a two-piece trapezoidal geometry approach. The performance of the composite two-piece trapezoidal piezoelectric PZT-PZN polycrystalline ceramic material is simulated using COMSOL Multiphysics. Results are analysed using the series configuration of a two-piece trapezoidal composite bimorph cantilever which vibrates at the first fundamental frequency. The two-piece trapezoidal composite beam designs resulted in a full-width half-maximum electric power bandwidth of 2.5 Hz while providing an electric power density of 16.81 mW/cm3 with a resistive load of 0.08 MΩ. The authors believe that these results could help design a piezoelectric energy harvester to provide local energy source which provides high electric power output.